A novel device to assess the oxygen saturation and congestion status of the gastric conduit in thoracic esophagectomy - Takeo Fujita; Takashi Shigeno; Daisuke Kajiyama; Kazuma Sato; Naoto Fujiwara; Hiroyuki Daiko (BMC Surgery, 2024)
Abstract Background In thoracic esophagectomy, anastomotic leakage is one of the most important surgical complications. Indocyanine green (ICG) is the most widely used method to assess tissue blood flow; however, this technique has been pointed out to have disadvantages such as difficulty in evaluating the degree of congestion, lack of objectivity in evaluating the degree of staining, and bias easily caused by ICG injection, camera distance, and other factors. Evaluating tissue oxygen saturation (StO2) overcomes these disadvantages and can be performed easily and repeatedly. It is also possible to measure objective values including the degree of congestion. We evaluate novel imaging technology to assess tissue oxygen saturation (StO2) in the gastric conduit during thoracic esophagectomy. Methods Fifty patients were enrolled, with seven excluded due to intraoperative findings, leaving 43 for analysis. These patients underwent thoracic esophagectomy for esophageal cancer. The device was used intraoperatively to evaluate tissue oxygen saturation (StO2) and total hemoglobin index (T-HbI), which guided the optimal site for gastric tube anastomosis. The efficacies of StO2 and T-HbI in relation to short-term outcomes were analyzed. Results StO2, indicating blood supply to the gastric tube, remained stable beyond the right gastroepiploic artery (RGEA) end but significantly decreased distally to the demarcation line (p <  0.05). T-HbI, indicative of congestion, significantly decreased past the RGEA (p <  0.05). Three patients experienced anastomotic leakage. These patients exhibited significantly lower StO2 (p <  0.01) and higher T-HbI (p <  0.01) at both the RGEA end and the demarcation line. Furthermore, the anastomotic site, usually within 3 cm of the RGEA’s anorectal side, also showed significantly lower StO2 (p <  0.01) and higher T-HbI (p <  0.01) in patients with anastomotic leakage. Conclusions The novel device provides real-time, objective evaluations of blood flow and congestion in the gastric tube. It proves useful for safer reconstruction during thoracic esophagectomy, particularly by identifying optimal anastomosis sites and predicting potential anastomotic leakage.